Pengalaman caregiver menantu perempuan bagi pengidap Demensia Parkinson dalam konteks budaya Tionghoa: Studi Fenomenologi - Fionna Gracia; Winarini Wilman D. Mansoer (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2023)
This study was conducted to gain understanding and meaning of a caregiver's experience in caring for her mother-in-law who suffers Parkinson's dementia. This is a phenomenological case study. Data were collected using the online semi-structured interview with a woman who is the main caregiver of her mother-in-law who suffers Parkinson's dementia. The results were presented in several themes regarding the participant’s experience and meaning. The conclusion from the results of this study is that there are various dilemmas faced in caring for parent-in-laws which then lead to conflicts between families. The existence of various factors contributing to developing caregiver burden on a caregiver who cares for parents-in-law with Parkinson's dementia.